2014
DOI: 10.1603/an14078
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Distribution of the Invasive Ant,Solenopsis invicta(Hymenoptera: Formicidae), in Cypress Savannas of North Carolina

Abstract: The ecological effects of invasive ants on ecosystems will depend largely on ant abundance. Cypress savannas of the southeastern United States have high conservation worth, supporting diverse and rare assemblages of species. Distance sampling was used to determine the abundance and distribution of colonies of the invasive ant, Solenopsis invicta Buren, in cypress savannas of two Carolina bays. Colonies were distributed throughout the savannas, save for areas of dense tree or shrub cover. Colony densities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…When two vehicles traveling in opposite directions pass each other, they will sometimes take turns or pull over onto the side, resulting in frequent soil disturbance. Roadsides or areas near roads are generally considered highly disturbed 10 , 11 , 34 , 38 , and narrow and disturbed areas suitable for RIFA establishment were demonstrated by Stiles and Jones 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When two vehicles traveling in opposite directions pass each other, they will sometimes take turns or pull over onto the side, resulting in frequent soil disturbance. Roadsides or areas near roads are generally considered highly disturbed 10 , 11 , 34 , 38 , and narrow and disturbed areas suitable for RIFA establishment were demonstrated by Stiles and Jones 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, the characteristics of roads are particularly conducive to RIFA invasion and establishment. Kelly and Sellers showed that roadsides had higher densities of RIFA than cypress savannas in a 2007 field survey in North Carolinas 10 . Tschinkel conducted a survey to identify the distribution of RIFAs in northern Florida.…”
Section: Introductionmentioning
confidence: 97%